GÉANT perfSONAR MDM-Based Circuit Monitoring in a Multidomain Environment - Liu, Feng; Yu, Hao; Naegele-Jackson, Susanne; Coulouarn, Tangui; Kulkarni, Trupti; Kleist, Josva; Hommel, Wolfgang; Dittmann, Lars (IEEE Communications Magazine, 2014)
Global research collaborations today require reliable and secure dedicated network connections to facilitate data communications between collaborating partners. To deal with the deluge of data, dedicated connections are needed to transport data in a highly efficient manner. Managing such links, which often cross multiple administrative domains with heterogeneous infrastructure, poses many compelling research challenges, one of which is interdomain network monitoring. In this article, a multidomain circuit monitoring system, CMon, is introduced. Using some services of GÉANT perfSONAR MDM, CMon is able to provide end-to-end circuit monitoring services with great flexibility, extensibility, and vendor independence, regardless of the underlying circuit provisioning systems. The architecture of CMon, by using measurement federations, can adapt to either changes in the circuit provisioning system or expansion of network size. © 2014 IEEE.
UnivIS-Import:2015-03-09:Pub.2014.zwiss.rrze.ksys.gantpe